Analysis of Electromechanical Delay in Neuromuscular Electrical Stimulation: Preliminary Results - Moreno, Yecid; Mosconi, Denis; Escalante, Felix M. [UNESP]; Siqueira, Adriano A. G. (Springer Nature, 2025)
In this paper, we propose to measure and characterize Electromechanical Delay (EMD) through a straightforward experiment that incorporates Functional Electrical Stimulation (FES) within a controlled motion environment. To this end, we have developed a data acquisition system specifically designed to synchronously detect stimulation events. The system was tested on both fatigued and non-fatigued quadriceps muscles. Our findings quantify the time between FES-induced and the torque response of the joint.